Sensitivity of Mangosteen Rind (Garcinia mangostana L.) Solution Toward Aeromonas hydrophila - Dian Fitria M; Iesje Lukistyowati; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTResearch was conducted from September to October 2014, at the labory Examination of Fish Disease, Fisheries and Marine Sciences Faculty of Riau University. The Purpose of this study was to determine the sensitivity of mangosteen rind (G. mangostana L.) as antimicrobial to A. hydrophila, the range of Minimal Inhibitory Concentration (MIC) and the lethal dose (LD50) mangosteen rind (G. mangostana L.) solution against to catfish (Clarias gariepinus) (10-13 cm) by immersion. The research method used doses 10 % (19 g/L), 20 % (38 g/L), 30 % (57 g/L), 40 % (76 g/L), 50 % (95 g/L), 60 % (114 g/L), 70 % (133 g/L), 80 % (152 g/L), 90 % (171g/L), 100 % (190 g/L). The results showed that mangosteen rind was effectively to inhibit the growth of bacterial A. hydrophila at a dose of 50 % (95 g/L) inhibitory zone of 13,65 mm, with the number of A. hydrophila colonies in TSA medium dose 50 % (95 g/L) is 30,6 x 108 cfu/mL. LD50 test was obtained in the dose mangosteen rind 4, 43 g/L.Key words : Garcinia mangostana L., Aeromonas hydrophila, antimicrobial, lethal dose